Aspects of the professional competences in the teaching staff graduated as health masters - Geovanis Olivares Paizan (Centro Provincial de Información de Ciencias Médicas, 2019)
Introduction: Professionalization of the university teaching staff has particular importance in the current university. Objective: To diagnose the evidences of the professional competences of the teaching staff graduated as health masters. Methods: A qualitative, descriptive and cross-sectional investigation was carried out, from April to June, 2018, to 59 members of the teaching staff, belonging to the Nursing-Technology Faculty of the Medical Sciences University in Santiago de Cuba, to whom a self-evaluation test was applied to determine their experiences related to the main specialty and the professional competences manifestations. Results: Of the 4 preset professional competences in the health masters programs, just the investigative one could be identified in the evidences of their performance. Equally, it was observed that most of the professors had more than 3 years of graduate as masters and so, they were considered as "professionals with experience" to exercise the competences. Conclusions: The teaching staff with different main specialties showed the difficulties that could exist in their professionalization, which will be validated in another stage of the study.